Oral Presentations Abstracts: MEDICAL REFUSAL: ETHICAL APPROACHES AND ISSUES FOR THE DIFFERENT SIDES OF THE CONCEPT - SOMEȘAN, Andreea Iulia (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 The bioethics analyzes and proposes ethical principles for the biomedical field. In major lines, we can consider the bioethics as having two important branches: biomedical research ethics and clinical ethics. The ethical approaches for each one of the mentioned contexts will bring different recommendation for the involved health professionals. In the clinical context, the medical refusal may come from the following sides: the patient’s refusal for certain prescriptions, the medical doctor’s refusal to accomplish some kinds of patient’s requests and medical refusal based on medical resources that can be allocate to one patient. What ethical principles and values may have these three sides of the medical refusal? The aim of the present paper is to evaluate the impact that each one of them may have on the relationship between the attending physician and the patient concerning their common goal, established at the beginning.